2014
DOI: 10.1088/0741-3335/56/9/094006
|View full text |Cite
|
Sign up to set email alerts
|

Fast ion confinement in the three-dimensional helical reversed-field pinch

Abstract: Fast ions are well confined in the stochastic magnetic field of the multiple-helicity (MH) reversed-field pinch (RFP), with fast ion confinement times routinely a factor of 5 to 10 higher than thermal confinement time. Recent experiments have examined the behavior and confinement of beam-born fast ions in the three-dimensional (3D) helical RFP state. In lower current discharges, where the onset of the helical state is uncertain, high power neutral beam injection (NBI) tends to suppress the transition to the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…Similarly, neutral particle analysis measurements resulting from fast ion charge-exchange losses decrease during the helical state. 6 Both tangential and radial lines of the site show distinct decreases with the growth in the n ¼ 5 core-resonant mode amplitude. The neutral particle analyzer signal is a lineaveraged measurement highly sensitive to particle pitch and neutral density.…”
Section: Tearing Mode Induced Transportmentioning
confidence: 95%
See 1 more Smart Citation
“…Similarly, neutral particle analysis measurements resulting from fast ion charge-exchange losses decrease during the helical state. 6 Both tangential and radial lines of the site show distinct decreases with the growth in the n ¼ 5 core-resonant mode amplitude. The neutral particle analyzer signal is a lineaveraged measurement highly sensitive to particle pitch and neutral density.…”
Section: Tearing Mode Induced Transportmentioning
confidence: 95%
“…The NBI deposited fast ions in MST mimic alpha particles in a burning reactor and act as a testbed for energetic particle physics in the 3D-RFP. 6 In comparison to alpha particles in a RFP-like reactor, MST's NBI born ions possess a similar gyroradius relative to the device size ðq fi =a $ 0:1), superthermal speed ðv fi =v th $ 13Þ, and superalfv enic speed ðv fi =v A > 1Þ but form a localized pitch-angle distribution due to the injection geometry in comparison to alpha particles' isotropic distribution. 7 The MST device (R 0 ¼ 1.5 m and a ¼ 0.5 m) produces deuterium RFP plasmas with total current I p ¼ 200-600 kA, central field strength jBj ¼ 0:2 À 0:5 T, and confined electron temperature T e ð0Þ ¼ 200 À 2000 eV.…”
Section: Introductionmentioning
confidence: 99%
“…The transition to a QSH state impacts also the confinement of fast ions, as described in Ref. 53. Here, it is shown that the helical equilibrium introduces neoclassical effects that reduce the fast ion confinement time with respect to the MH state.…”
Section: Thermal Electron Time Evolution and High Energy Electron Genmentioning
confidence: 71%
“…Indeed, Note: Contributed paper, published as part of the Proceedings of the 21st Topical Conference on High-Temperature Plasma Diagnostics, Madison, Wisconsin, USA, June 2016. a) Electronic mail: bonofiglo@wisc.edu neutral particle analysis and measured fusion neutron flux indicate enhanced fast ion transport in the plasma core at the RFP's transition to a 3D state and with beam-driven, bursting magnetic modes. [7][8][9] By including a FILD in our diagnostic suite, we wish to gain further insight into these events. This paper will discuss the design of a high-pitch FILD for a RFP in Section II and present the initial measurements and findings of the device in Section III.…”
Section: Introductionmentioning
confidence: 99%